Investors' personal characteristics and trading decisions under distressed market conditions - Liron Reiter-Gavish; Mahmoud Qadan; Joseph Yagil (Borsa Istanbul Review, 2022)
Using data for about 50,000 actual household investment accounts, we document that financial advice reduced investors’ tendency to leave the stock market during the market crash of 2008 and had a positive correlation with their decisions to return to the market. In addition, we provide a comprehensive analysis of the role of investors' economic and demographic characteristics in their decision to sell all of their portfolio securities, or in contrast, to hold or even increase the value of their portfolio. Finally, we find that being divorced increases the probability of leaving the market, while singles are less likely to leave the market during a crisis.